SYURA DAN MUSDAT: INTEGRASI MUSYAWARAH ISLAM DAN ADAT DAYAK - Rizka Fadzillah; Rafika Yuli; Tiara Gita Safitri (Makkah: Journal Of Islamic Studies, 2025)
This study examines musyawarah (deliberation) as a fundamental value deeply embedded in the social, political, and cultural life of Indonesian society, and analyzes its relevance from both Islamic perspectives and Dayak customary traditions. The objectives of this research are to explore the concept of musyawarah based on key Qur’anic verses Ali Imran 159, Ash-Shura 38, and Al-Baqarah 233 and to investigate musdat, the Dayak traditional deliberation system. This research employs a qualitative descriptive approach using content analysis of classical and contemporary Qur’anic exegesis, supported by anthropological literature on Dayak customary law. The findings demonstrate that the Islamic principle of syûrâ emphasizes compassion, dialogue, and collective wisdom in decision-making, while musdat reflects a restorative, consensus-based conflict resolution model centered on communal harmony. The study reveals strong normative and cultural coherence between syûrâ and musdat, showing that deliberation is not only a theological principle but also a deeply rooted local practice within Indonesian indigenous communities. These findings imply that integrating religious and local wisdom can contribute to the development of culturally grounded and socially responsive conflict resolution frameworks in multicultural societies such as Indonesia.